M USANG DALAM K A R Y A SENI GRAFIS TEKNIK (LINOLEUM CUT) - Wahyu Pratama; Yofita Sandra (Serupa The Journal of Art Education, 2020)
The creation of this final work aims to visualize the ferret behavior of human activities at night related to human behavior today into the form of graphic art works (linoleum cut). Showing a variety of human behavior that is mostly done today. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. Author Successfully Manifests 10 works with the title: Intercourse, Drunkards, Gadgets Addictions, Crazy Assets, Thieves, Authorities, King of Gamblers, Street Kings, Forgotten Times, Lord of War.Keywords: Weasel, Graphic Art, Linoleum Cut